Determination of unacceptable HLA antigen mismatches in kidney transplant recipients. (25th February 2022) - Ziemann, Malte; Suwelack, Barbara; Banas, Bernhard; Budde, Klemens; Einecke, Gunilla; Hauser, Ingeborg; Heinemann, Falko Markus; Kauke, Teresa; Kelsch, Reinhard; Koch, Martina; Lachmann, Nils; Reuter, Stefan; et al.
Abstract : With the introduction of the virtual allocation crossmatch in the Eurotransplant (ET) region in 2023, the determination of unacceptable antigen mismatches (UAM) in kidney transplant recipients is of utmost importance for histocompatibility laboratories and transplant centers. Therefore, a joined working group of members from the German Society for Immunogenetics (Deutsche Gesellschaft für Immungenetik, DGI) and the German Transplantation Society (Deutsche Transplantationsgesellschaft, DTG) revised and updated the previous recommendations from 2015 in light of recently published evidence. Like in the previous version, a wide range of topics is covered from technical issues to clinical risk factors. This review summarizes the evidence about the prognostic value of contemporary methods for HLA antibody detection and identification, as well as the impact of UAM on waiting time, on which these recommendations are based. As no clear criteria could be determined to differentiate potentially harmful from harmless HLA antibodies, the general recommendation is to assign all HLA against which plausible antibodies are found as UAM. There is, however, a need for individualized solutions for highly immunized patients. These revised recommendations provide a list of aspects that need to be considered when assigning UAM to enable a fair and comprehensible procedure and to harmonize risk stratification prior to kidney transplantation between transplant centers.